Pediatric Scald Injuries Sustained From Instant Soup and Noodle Products. (January 2021) - Allen, Courtney E.; Figueroa, Janet; Agarwal, Maneesha; Little, Wendalyn K.
Background and Objective . Scald burns are a major cause of pediatric burn injuries. Instant soups have been identified as one source of these injuries. This study aims to quantify and characterize these injuries in pediatric patients. Methods . Ten-year query of National Electronic Injury Surveillance System (NEISS) database identified instant soup- and noodle-related scald burns in children aged 4 to 12 years. Data included patient demographics, injured body part, case narratives, and emergency department disposition. Results . A total of 4518 cases were identified, yielding an estimate of 9521 cases/year in the United States. Younger children were affected more than the older. Trunk was the most commonly burned body area. Approximately 10% of injuries required admission or transfer for further care. Conclusion . Instant soup and noodle products are a common cause of pediatric scald burns, potentially injuring 25 children per day in the United States and leading to high rates of health care utilization.